The Effectiveness of the Crowdsourcing Concept in Human Resource Management in the Online Motorcycle Taxi Business on the Satisfaction of Partners and Service Users - Mimin Pembayuningtyas; Purnomo, Hery; Dodi Kusuma Hadi Soejoko (Open Access Indonesia Journal of Social Sciences, 2023)
Crowdsourcing is a concept where complex tasks or problems can be solved through collaboration with a group of people online. In the context of the online motorcycle taxi business, crowdsourcing has proven to be a very effective tool for managing human resources. This is due to several factors, including the wide operational scale, speed of service, and the complexity of user requests. This study aimed to explore the effectiveness of the crowdsourcing concept in human resource management in the online motorcycle taxi business on the satisfaction of partners and service users. The application of crowdsourcing in HR management in the online motorcycle taxi business has proven effective in dealing with the challenges faced by this industry. Labor flexibility, cost efficiency, and access to diverse talent are some of the main benefits of crowdsourcing. However, companies must still pay attention to important management aspects such as service quality and good working relations to ensure the success and long-term effectiveness of this crowdsourcing strategy.